PENGARUH MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PENGUSAHA BOLEN PIA BALEDONO DI KABUPATEN PURWOREJO (Prospect : Jurnal Manajemen dan Akuntansi, 2021)
The aim of this research is to find out whether there is a positive and significant influence between motivation on employee performance at UMKMBolen Pia Baledono in Purworejo Regency. The population in this research is all employees at UMKM Bolen Pia Baledono Purworejo, totaling 26 employees, while the sampling technique uses a saturated sample where all members of the population are sampled, so the total research sample is 26 employees. Data collection techniques in this research were obtained by observation, interviews, questionnaires, documentation and literature study techniques. Data regarding research variables is obtained through questionnaires or questionnaires distributed to respondents to provide responses to questions/statements in the questionnaire, then it will be analyzed using simple regression analysis, coefficient of determination, and T test. The results of simple regression are Y′ = 6.215 + 0.638X, meaning that if the work motivation value is increased by 1 point, then the size of the employee performance variable is 6.215. The results of calculating the coefficient of determination show that the R square is 43.8%, this figure means that the motivation variable contributes 43.8% to the performance variable and the remaining 56.2% of employee performance is influenced by other variables such as employee perception, employee personality, employee resources. , business leadership, and employee discipline. The results of the t test show that the t value is greater than t table or (4.324 > 2.063) and the significance level is (0.000 < 0.05), so H0 is rejected and Ha is accepted, which means there is a positive and significant influence between work motivation (X) on performance. employees (Y) at UMKM Bolen Pia Baledono Purworejo..